Pendampingan Kegiatan Rutinan Diba’ Sebagai Upaya Menumbuhkan Karakter Cinta Nabi Saw Bagi Santri Di Pondok Pesantren Kauman Lasem: Assistance in Diba' Routine Activities as an Effort to Build the Character of the Prophet's Love for Santri at the Kauman Lasem Islamic Boarding School - Farida Isroani; Roudlotun Ni’mah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
Loving the Prophet Muhammad is an obligation for all Muslims. Love for the Prophet Muhammad SAW as a source of strength in the heart and is often referred to as the power of love or the power of love. There are many verses of the Qur'an and Hadith that explain the recommendation to love the Prophet Muhammad. One way to manifest love for the Prophet Muhammad is through the reading of shalawat. The purpose of this study was to find out: (1) How to Efforts to Grow the Prophet's Love Character for Santri through Diba' Activities. (2) What are the Supporting and Inhibiting Factors in Efforts to Grow the Prophet's Love Character for Santri through Diba'/ To achieve the above objectives, descriptive qualitative research is used. Data collection techniques through observation, interviews, and documentation. Meanwhile, to analyze the data, the author does it by examining all the data, reducing the data, presenting the data, and concluding/verifying the data. The results showed that: the character of the love of the Prophet Muhammad SAW has been well realized in the Pondok Pesantren Putri. The realization of the love character of the Prophet Muhammad SAW has been realized in a weekly activity program. Efforts to grow the character of the love of the Prophet Muhammad SAW are supported by the activity of reading Shalawat Diba ', this activity has been running since the Pondok Pesantren was established. The implementation was on Thursday night Friday and was attended by all female students and clerics who took shelter at the Al Rosyid Islamic Boarding School. The supporting factors in an effort to grow the character of the Prophet's love are facilities and infrastructure, a relevant environment, a strong will, the right goals and intentions, encouragement and motivation. To balance it, there are also inhibiting factors, namely the implementation time is quite long, saturation, lack of creation and innovation.